PENINGKATAN SKILL CALON WIRAUSAHA PETANI TOMAT MENGGUNAKAN TEKNOLOGI AGRO MANUFACTURING UNTUK MEMANFAATKAN SISA PANEN YANG TERBUANG - Suprayitno Suprayitno; Nurhanifam Nurhanifam (Publisher UPT P2M Politeknik Negeri Malang, 2015)
IBM Program Implementation united a concrete form of community service performed in order to transfer skills to prospective Producties Agro Manufacturing entrepreneurial farmers are capable of processing tomatoes into Produkt Raw materials processed include: sauce, Jam, Jelly, & Candied Fruit tomatoes utilize relatively Results for harvest wasted.Post prospective entrepreneurs successfully mastered the skill Producties processing tomatoes are good, they are expected to brave pioneering independence practicing / economy, besides that in the long term they are expected to create opportunities around Enterprises baggy citizens, who temporarily united the average dependent on the agriculture sector.After the briefing given for entrepreneurial Producties ability of the process, financial administration include therein well as managerial aspects of marketing, especially supported by Produkt Produkt-are already expected to have PIRT, they are expected to efficiently distribute the results of their production to the consumer market As well as the formal market ( Super Market in Mini Market). The last candidate entrepreneurs united expected to diversify Results of production, making it more acceptable to consumers varied teeth.